Environmental Influence on the Chromosome Synapsis in Solanum khasianum and Scope for Chromosome Manipulation (Bangladesh Journal of Genetics and Biotechnology, 2009)
Key words: Solanum khasianum, desynapsis, Asynapsis, Pachytene Bangladesh j. genet. biotechnol. 7(1&2): 11-13 2006 (June & December)